Unusual angular dependence of tunneling magneto-Seebeck effect - Heiliger, Christian; Czerner, Michael; Liebing, Niklas; Serrano-Guisan, Santiago; Rott, Karsten; Reiss, Günter; Schumacher, Hans W.; Justus Liebig University Giessen (My University, 2018)
We find an unusual angular dependence of the tunneling magneto-Seebeck effect (TMS). The conductance shows normally a cosine-dependence with the angle between the magnetizations of the two ferromagnetic leads. In contrast, the angular dependence of the TMS depends strongly on the tunneling magneto resistance (TMR) ratio. For small TMR ratios we obtain also a cosine-dependence whereas for very large TMR ratios the angular dependence approaches a step-like function. The origin is that the cosine-dependent transmission function enters in the denominator of the definition of the Seebeck coefficient. Although the TMR and TMS are disconnected with respect to their magnitude the size of the TMR effect can be deducted from the angular dependence of the TMS effect.
Keywords: ddc:530